Nutritional aspects and food management in the control of Polycystic Ovarian Syndrome (Research, Society and Development, 2022)
To evaluate the nutritional aspects and nutritional management in Polycystic Ovary Syndrome (PCOS), describing its pathology, clinical manifestations, diagnosis, treatment and nutritional approach in Polycystic Ovary Syndrome. This is a non-systematic literature review study with articles associated with the Polycystic Ovary Syndrome (PCOS) theme, from the scientific databases Pubmed, Scielo, Tripdatabase and Google Scholar. The practice of physical exercises associated with a change in lifestyle (diet) and follow-up with a gynecologist has been considered a beneficial advance for the control of symptoms in women with PCOS. In this way, it is concluded that a hypocaloric diet is indicated, with foods with a low glycemic index, since they can act positively in the PCOS framework. Finally, some supplements such as omega 3, inositol, n - acetylcysteine ​​and vitamin D can help in the control and symptoms of PCOS.